Implementation Of Strengthening Character Education In Students Of The Social Science Education Study Program. - Karwur, Hermon Maurits; Lobja, Xaverius E.; Andaria, Kalvin S. (SHS Web of Conferences, 2022)
The purpose of the study was to determine the implementation of strengthening character education for students of the Social Sciences Education study program, FIS Unima. In achieving these objectives, this research was carried out using qualitative research methods, and data collection techniques including observation, interviews, documentation, and triangulation. The research informant is the Social Sciences Education lecturer at FIS Unima. The stages of data analysis include: data reduction, data display, and conclusion drawing/verification. The results showed that a) the efforts made in understanding the character of Social Studies Education students were: formulating semester learning plans, studying and understanding student characters, and mapping student characters; b) the main values described by the teacher in the semester learning plans and in the learning process include the basic ethical values: 1) devotion to God, 2) responsibility, 3) nationalism, 4) independence, 5) innovation, 6) democracy and 7) mutual respect. c) Important efforts made in strengthening character education for students include: 1) through the formulation of learning outcomes, 2) through the formulation of graduate competencies, 3) through the learning process, 4) mentoring activities, and 5) research activities; d) students of the Social Sciences Education study program gave a positive response or response to all the efforts we made.